Efektivitas Larutan Bawang Putih dalam Pengendalian Larva Aedes Agypti (Media Kesehatan Masyarakat Indonesia, 2019)
Efforts to control Dengue Hemorrhagic Fever using insecticides pose a risk of resistance to mosquitoesand are not environmentally friendly, so an alternative method of controlling Aedes agypti larvae based onnatural materials is needed. This study aims to compare the effectiveness of abate powder and garlic solution incontrolling Aedes aegypti larvae with various concentrations, by using true experimental design with a completelyrandomized design. The samples was Aedes aegypti larvae stage III and IV with total sample of 25 larvae whichput into abate powder and garlic solution with a concentration of 20 mg/100 ml, 40 mg/100 ml, 60 mg/100 ml,80 mg/100 ml, and 100 mg/100 ml. Abate powder reaction speed is faster (40 minutes) than garlic solution (24hours). The number of straight larvae deaths with concentrations of abate and garlic powder, the highest mortalityof larvae at 24 hours. Based on the Mann Whitney test, there was no significant difference between abate powderand garlic solution in controlling Aedes agypti larvae at a concentration of 100 mg in 24 hours observation (p =1,000). Therefore, abate powder and garlic solution at a concentration of 100 mg had the same effectiveness incontrolling larvae of Aedes agypti within 24 hours
Keywords: Bubuk abate; bawang putih; larva aedes agypti